Perancangan, Simulasi dan Analisis Harmonisa Rangkaian Inverter Satu Fasa - Faizal Arya Samman; Rizkiyanti Ahmad; Mutiah Mustafa (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2015)
This paper presents the design, simulation and harmonic analysis of a one-phase inverter circuit. The impacts of the used passive filter and the used of snubber on the quality of the voltage output of the one-phase inverter, which used full-bridge configuration, were described in this paper. The passive LC filter using the combination of an inductor and capacitor was configured in parallel with the load, such that the voltage output waveform can be modified from modulated pulse waveform into purely sinusoidal waveform. The total harmonic distortion (THD) of the voltage output can be well reduced by using such LC passive filter. The circuit was designed and modeled in SPICE program code, then simulated and analysed. The result shows that the use of Zener Diode as a circuit snubber is able to improve the power characteristic and voltage magnitude of the designed inverter as compared to commonly used Diode.